The specificity of the Eating Disorder Inventory. - Cooper, Z; Cooper, P; Fairburn, C (1985)
A self-report measure, the Eating Disorder Inventory (EDI), has recently been published. An examination of the responses on the EDI of a sample of psychiatric out-patients who did not have eating problems revealed that many of its subscales may be non-specific in character reflecting the general level of psychological disturbance.